ADMINISTRAS KEPENDUDUKAN DIKEPENGHULUAN AKAR BELINGKAR KECAMATAN TANJUNG MEDAN TAHUN 2018-2020 - Andrizal Zainal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Population administration is a very important thing and also plays a role in development, where the population administration system can be known about population data and information that is in accordance with the condition of the population and about the condition of the area where the population lives. Population administration errors still occur in many places in Indonesia, especially in border areas. As happened in the Akar Belingkar village, Tanjung Medan district, the Akar Belingkar community, but their residency documents are not in the name of the Akar Beligkar village.This study aims to find out how the population administration in Akar Belingkar village is. The research approach used is qualitative with descriptive analysis method by describing phenomena and data accurately. The location of the research is in Akar Belingkar village, Tanjung Medan District, Rokan Hilir Regency. The types and sources of research data are divided into primary data using purposive informant retrieval techniques and secondary data in the form of supporting data related to population administration in the Akar Belingkar village. Data collection techniques used by interview and documentation.The results of this study are, first, the population administration in the Akar Belingkar village experienced a problem where there were some residents/communities in the hamlet of Simpang 3 Perdamaian, Akar Belingkar village who did not have a resident document (KTP) and did not have the status of a Akar Belingkar resident. The two services carried out by the Akar Belingkar village  apparatus have not met the service standards as obtained in the field, namely the ability of the apparatus; with the most backgrounds, namely high school education and in order to improve work ability it is necessary to be included in several employee trainings. Clarity of information about the services provided by posting some information on the information board provided Keywords: Population Administration, Services, Village Government